Venetoclax plus hypomethylating agents versus intensive chemotherapy for hematological relapse of myeloid malignancies after allo-HSCT - Chen, Zhangjie; Zhen, Sisi; Zhang, Tingting; Shen, Yuyan; Pang, Aiming; Yang, Donglin; Zhang, Rongli; Ma, Qiaoling; He, Yi; Wei, Jialin; Zhai, Weihua; Chen, Xin; et al. (Frontiers in Oncology, 2023)
Introduction Since allogeneic stem cell transplantation (allo-HSCT) is considered one of the curative treatments for acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), hematological relapse following allo-HSCT remained a crucial concern for patients’ survival. Methods We retrospectively compared patients who received venetoclax plus hypomethylating agents (VEN+HMA, n=23) or intensive chemotherapy (IC, n=42) for hematological relapse of myeloid malignancies after allo-HSCT. HMA selection included decitabine (n=2) and azacitidine (n=21), and combined donor lymphocyte infusion was administered to 21 and 42 patients in VEN+HMA and IC groups, respectively. Results Median age of all patients was 39 (16-64) years old. Overall response rates, including complete response (CR), CR with incomplete recovery of normal neutrophil or platelet counts (CRi) and partial response (PR), were not significantly different between VEN+HMA and IC groups (60.1% versus 64.3%, P=0.785). CR/CRi rate was 52.2% in VEN+HMA and 59.5% in IC group (P=0.567). The rate of relapse after response was 66.7% in VEN+HMA group and 40.7% in IC group (P=0.176). Median overall survival was 209.0 (95%CI 130.9-287.1) days for VEN+HMA group versus 211.0 (95%CI 28.7-393.3) days for IC group (P=0.491). The incidence of lung infection (17.4% versus 50.0%, P=0.010), thrombocytopenia (73.9% versus 95.2%, P=0.035) and acute graft-versus-host disease (aGvHD) (50.0% versus 13.0%, P=0.003) was significantly higher in IC group. Discussion In conclusion, VEN+HMA is not inferior to IC regimen in terms of improving response and survival, and is associated with a lower incidence of adverse events and aGvHD. However, further research is required to enhance long-term survival.